Princess of Byzantium - Allen, Josephine ([Torrens Park, S. Aust.] : Jacobyte Books, 2000)
Historical romance set in Constantinople. Danger and intrigue surround the Princess Zoe of Byzantium and the handsome Magyar she encounters.